Poder e discurso na ficção científica distópica: o regime de verdade de Fahrenheit 451 - Silva, Willy Nascimento (2022)
Fahrenheit 451 (1953), a novel by Ray Bradbury published in the post-war period, draws attention for the way it denounces the contradictions inherent in industrial societies that emerged from the 1950s onwards, evidencing more “refined” power strategies than those represented in the classic dystopias of the early 20th century. These strategies, which include devices such as the cultural industry, the school and the publicity, demonstrate that it is not only investing bodies that one conduct individual behaviors, but producing effects of truth within discourses that, by themselves, are obeyed. Therefore, this work aims to verify how power operates through these discourses in order to establish the truth regime of dystopian society. For that, the notions of utopia, eutopia and dystopia (BACCOLINI; MOYLAN, 2003; CLAEYS, 2010; 2013; 2017; MOYLAN, 2000a; 2000b; 2014; SARGENT, 1975; 1994; 2006); the link between utopian fiction and science fiction (SUVIN, 1979; 1988; 2003; 2010) – considering that Fahrenheit 451 occupies an intersection zone between the two: dystopian science fiction –; and the stance that both take on scientific progress (BOOKER, 1994; CLAEYS, 2017; ROBERTS, 2018) are explored. Furthermore, the relationship between science and power (HABERMAS, 2014; MARCUSE, 2015); the formation of the utopian discourse (FOUCAULT, 1987; 1999; 2006; 2019a); and the definition of an economy of power that combines physical controls (FOUCAULT, 2014), psychological controls (ADORNO; HORKHEIMER, 1985; DEBORD, 1997; ILLICH, 2018; VINICIUS, 2014) and security devices (FOUCAULT, 2008; 2019d) are discussed. The arguments built in the theoretical sections are resumed from a critical analysis of Fahrenheit 451, whose results indicate that the truth regime of the society represented in the work would be supported by power strategies such as the spectacularization of human relations, the massification of culture and the rebellion fetishization.